Evaluation of personnel-adjusted added value: Estimating its relationship with future profit in Japan - Hiroki Iwamoto; Hideo Suzuki (Cogent Economics & Finance, 2021)
Personnel-adjusted added value (PAV) is an index to measure human resource management for internal purposes. In this study, the possibilities and limitations of PAV using external estimates are investigated. To measure the effectiveness of PAV, it is compared with the general added value. This proves the effect of the personnel adjustment. The relationship between future performance and PAV (and added value), including other control variables, are statistically analysed by hierarchical linear modelling. The essence of PAV is to separate the basic labour costs from the company-specific personnel costs. To calculate PAV from outside an enterprise, the basic labour costs should be estimated. For this purpose, in addition to financial data, this study uses survey data on recruitment and employment in Japan. Statistical analysis is applied to the 2008-2016 longitudinal company data of 569 Japanese companies. We find that PAV, a management indicator that includes the adequacy of human resource management, is a useful factor related to future performance.
Keywords: 330; human resource management; intellectual capital; key performance indicator; Personnel-adjusted added value